Evaluation of ultrasound accuracy in thyroid mass measurement and its impact on 131I treatment for Graves’ disease - Li, Xiangxiang; Han, Xu; Liu, Nan; Wang, Shen; Zheng, Hongyuan; Ma, Ziyu; Zhang, Ruiguo; Jia, Qiang; Zheng, Wei (Frontiers in Endocrinology, 2025)
BackgroundThyroid mass is crucial for 131I treatment of Graves’ disease (GD). However, the accuracy of ultrasound (US) - based thyroid mass measurement remains controversial.MethodsThis retrospective study included patients who underwent thyroid US and CT scans. The differences correlation, and agreement in thyroid mass measurements between the two methods were analyzed. Data from GD patients who received their first 131I treatment were collected and evaluated at a 6-month follow-up. Regression analyses identified clinical factors for treatment efficacy and developed a predictive model.ResultsA statistically significant difference was observed in thyroid mass measurements exceeding 20 g between US and CT. (Z = -11.493, P<0.001). Despite a strong correlation between the two methods (r = 0.9809, P=0.001), the average relative error remained substantial (0.19 ± 11.65%). Poor agreement was observed between CT and US (mean bias: 16.65g; ICC = 0.179, p = 0.087). Disease duration, FT4 level, 24 - hour radioactive iodine uptake, 131I dose and thyroid mass were identified as independent risk factors influencing the efficacy of the initial 131I treatment (p<0.05). Based on these factors, a predictive model was developed and evaluated using ROC curves, DCA and CAL. The model demonstrated an AUC of 0.663 (95% CI = 0.631-0.695).ConclusionUS may underestimate the true thyroid mass in large-mass cases; therefore, CT calibration is recommended before initiating 131I treatment. The proposed predictive model provides valuable guidance for optimizing initial 131I treatment in patients with GD.